Ventilation before Umbilical Cord Clamping Improves the Physiological Transition at Birth - Bhatt, Sasmira; Polglase, Graeme R.; Wallace, Euan M.; te Pas, Arjan B.; Hooper, Stuart B. (Frontiers in Pediatrics, 2014)
The transition from a fetus to a neonate at birth represents a critical phase in our life. Most infants make this transition without complications, but preterm infants usually require some form of assistance due to immature cardiopulmonary systems that predispose them to lifelong sequelae. As the incidence of preterm birth is increasing, there is now an urgent need for the development of management strategies that facilitate this transition, which will likely include improved strategies for the management of the maternal third stage of labour. For instance, recent studies on the physiological transition at birth have led to the discovery that establishing ventilation in the infant before the umbilical cord is clamped greatly stabilizes the cardiovascular transition at birth. While most benefits of delayed clamping have previously been attributed to an increase in placenta to infant blood transfusion, clearly there are other significant benefits for the infant, which are not well understood. Nevertheless, if ventilation can be established before cord clamping in a preterm infant, the large adverse changes in cardiac function that normally accompanies umbilical cord clamping can be avoided. As preterm infants have an immature cerebral vascular bed, large swings in cardiovascular function places them at high risk of cerebral vascular rupture and the associated increased risk of mortality and morbidity. In view of the impact that cord clamping has on the cardiovascular transition at birth, it is also time to re-examine some of the strategies used in the management of the third stage of labour. These include the appropriate timing of uterotonic administration in relation to delivery of the infant and placenta. As there is a lack of evidence on the effects these individual practices have on the infant, there is a necessity to improve our understanding of their impact in order to develop strategies that facilitate the transition to newborn life.